2016
DOI: 10.1037/edu0000045
|View full text |Cite
|
Sign up to set email alerts
|

A latent profile analysis of math achievement, numerosity, and math anxiety in twins.

Abstract: Underperformance in math is a problem with increasing prevalence, complex etiology, and severe repercussions. This study examined the etiological heterogeneity of math performance in a sample of 264 pairs of 12-year-old twins assessed on measures of math achievement, numerosity and math anxiety. Latent profile analysis indicated five groupings of individuals representing different patterns of math achievement, numerosity and math anxiety, coupled with differing degrees of familial transmission. These results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 68 publications
4
43
0
Order By: Relevance
“…For instance, a decreased performance in symbolic magnitude processing was observed in high-math anxious adults by Núñez-Peña and Suárez-Pellicioni [81] and by Maloney and colleagues [71,72], who additionally found that WM intervened as a mediator in the relation between symbolic skills and math anxiety. In contrast, no significant association emerged between math anxiety in the few studies that adopted non-symbolic tasks to assess magnitude processing in children [43,47]. Finally, in a study with young adolescents, none significant relation with math anxiety surfaced either with symbolic or non-symbolic estimation acuity [112].…”
Section: The Relation Between Cognitive and Affective Factorsmentioning
confidence: 78%
See 1 more Smart Citation
“…For instance, a decreased performance in symbolic magnitude processing was observed in high-math anxious adults by Núñez-Peña and Suárez-Pellicioni [81] and by Maloney and colleagues [71,72], who additionally found that WM intervened as a mediator in the relation between symbolic skills and math anxiety. In contrast, no significant association emerged between math anxiety in the few studies that adopted non-symbolic tasks to assess magnitude processing in children [43,47]. Finally, in a study with young adolescents, none significant relation with math anxiety surfaced either with symbolic or non-symbolic estimation acuity [112].…”
Section: The Relation Between Cognitive and Affective Factorsmentioning
confidence: 78%
“…The finding related to the mediating role of the ANS measure of approximate addition is indeed more innovative, given that the few studies targeting the relation between ANS and anxiety had different aims, and mainly focused on math anxiety rather than on general anxiety (e.g., [43,47,112]). Importantly, and different from our findings, the majority of prior studies did not observe any significant involvement of the ANS components, at least when expressed by non-symbolic skills.…”
Section: Relation Between Cognitive and Affective Components In Determentioning
confidence: 99%
“…The resulting sample was predominantly Caucasian (greater than 90%) and comprised a wide range of SES. Twins were assessed on a range of cognitive skills over 7 years and 9 waves of testing (Hart et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Some recent work investigating mathematical development through a neuroconstructivist lens (e.g., Ref ) serves as a useful example of how a more integrative approach could inform our understanding of spatial development and sex differences in spatial thinking. Hart and colleagues used a latent class analysis in a large twin study to explore familial transmission—representing shared genes and environments—of different profiles of cognitive and affective correlates of math achievement in 12‐year olds.…”
Section: Factors Contributing To Sex Differences In Spatial Skillmentioning
confidence: 99%